2022
DOI: 10.21511/bbs.16(4).2021.19
|View full text |Cite
|
Sign up to set email alerts
|

The effect of working capital management and credit management policy on Jordanian banks’ financial performance

Abstract: This study investigated the impact of Working Capital Management (WCM) and Credit Management Policy (CMP) on the Financial Performance (FP) of Jordanian banks (JB). The study data were obtained from 16 Jordanian banks listed on the Amman Stock Exchange (ASE) between 2017 and 2020. The study used panel data to investigate the relationship between the two independent variables, WCM and CMP, and the dependent variable FP; 64 financial reports to Jordanian banks were analyzed to measure this relationship. To test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 16 publications
4
18
1
Order By: Relevance
“…(2017) discovered that APP has an adverse effect on the profitability of Vietnamese SMEs. The findings of other studies like Gołaś (2020) and Abdulnafea et al . (2022) suggested that APP significantly and negatively influenced firm profitability.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 51%
See 2 more Smart Citations
“…(2017) discovered that APP has an adverse effect on the profitability of Vietnamese SMEs. The findings of other studies like Gołaś (2020) and Abdulnafea et al . (2022) suggested that APP significantly and negatively influenced firm profitability.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 51%
“…(2017), Gołaś (2020), Ibrahim and Isiaka (2021), Hofmann et al . (2022), Abdulnafea et al . (2022) and Urhoghide and Korolo (2022).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The financial performance of a bank is expressed in quantitative values or measures expressed in monetary units such as the rate of return on equity and the rate of return on investment. Measuring financial performance results in the formulation of rules and mechanisms that help banks improve their strategies, as well as an assessment of achieving goals and rewarding managers (Abdulnafea et al, 2022). Financial performance is defined as the degree to which the bank's financial goals are achieved (Nguyen et al, 2021).…”
Section: Concept Of Financial Performancementioning
confidence: 99%
“…The financial performance during a certain period can be used to measure the bank's performance in comparison with the banks operating in the same sector (Ehiedu & Toria, 2022). Financial performance is the product of all the bank's operations and strategies, as the financial performance of banks provides information to develop their strategic plans (Abdulnafea et al, 2022). Kurawa and Shuaibu (2022) defined financial performance as a measure of expressing the general financial productivity of banks over a specific financial period.…”
Section: Concept Of Financial Performancementioning
confidence: 99%